2023
DOI: 10.3389/feart.2022.1029429
|View full text |Cite
|
Sign up to set email alerts
|

Research and application of pressure relief and permeability improvement in high gas outburst mines by directional drilling and hydraulic jet

Abstract: Efficient gas extraction technology is an important topic for low permeability and high gas outburst coal seam. Based on the engineering background of Hudi Coal Mine with the soft and hard coal seams and the existing hydraulic permeability enhancement technology, a new construction process to improve coal seam permeability was proposed to effectively reduce coal seam gas content and the risk of coal and gas outburst. In this measure, the roadway in floor was replaced with a directional main borehole, direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Based on common hydraulic fracturing, Zhai et al proposed the pressure relief and permeability improvement technology of pulsating hydraulic fracturing, which improved the concentration and flow of borehole gas extraction in low permeability coal seam [11]. Combined with the existing hydraulic reflection improvement technology, Li et al put forward a new method of soft coal mining along the soft sub-layer by using directional drilling rig and hydraulic jet, effectively reducing the risk of coal and gas outburst [12]. Based on the theory of gas flow and coal body deformation, Zhang et al found that the gas pressure in cracks of soft coal seam decreases under high pressure abrasive water jet reflection improvement, and the extraction volume is three times higher than that of conventional drilling [13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on common hydraulic fracturing, Zhai et al proposed the pressure relief and permeability improvement technology of pulsating hydraulic fracturing, which improved the concentration and flow of borehole gas extraction in low permeability coal seam [11]. Combined with the existing hydraulic reflection improvement technology, Li et al put forward a new method of soft coal mining along the soft sub-layer by using directional drilling rig and hydraulic jet, effectively reducing the risk of coal and gas outburst [12]. Based on the theory of gas flow and coal body deformation, Zhang et al found that the gas pressure in cracks of soft coal seam decreases under high pressure abrasive water jet reflection improvement, and the extraction volume is three times higher than that of conventional drilling [13].…”
Section: Introductionmentioning
confidence: 99%